Eating novel foods: An application of the Theory of Planned Behaviour to predict the consumption of an insect-based product. (July 2017) - Menozzi, Davide; Sogari, Giovanni; Veneziani, Mario; Simoni, Erica; Mora, Cristina
Highlights: The TPB explains 78% and 19% of the variance in eating insects-based food intention and behaviour. Attitude predicts intention, and intention is the main predictor of eating insects-based food. Beliefs on positive effects on health and environment affect intention of eating insects-based food. Gender and background studies correlate with intention to eat insects-based food. Attitude and intention improved after tasting the insect-based food product. Abstract: Insects are a potential ingredient of food preparations, providing nutrients (e.g. proteins) with a low environmental impact. Despite the benefits, consumers in Western countries generally reject the practice of eating insects. This work aims to measure the intention to and the behaviour of eating novel food products containing insect flour in the next month. The novel food product of choice was a chocolate chip cookie with an ingredient from edible insects (10% of cricket flour), which might be considered as an enriched-in-proteins substitute of traditional cookies. We investigated 231 Italian young adults using the Theory of Planned Behaviour (TPB), assuming that behaviour, given sufficient control, is guided by intention. We used the observation of the actual tasting of the novel food product as a measure of prospective behaviour. The TPB model accounted for 78% of the variance in intention and 19% of the variance in behaviour. Attitude and perceived behavioural control (PBC) are statistically significant predictors of intention, while intentions and PBC are of behaviour. Beliefs that eating an insect-based food product has positive effects on health and the environment significantly affect attitudes and intention. The main barriers preventing the intention of eating food products containing insect flour are the sense of disgust arising from seeing insects around, the incompatibility with local food culture and the lack of products in the supermarket. Interventions may consider targeting behavioural control, developing food products close to the Western dietary pattern, such as bakery products containing insect flour, and signalling the positive effects on health and the environment.